Coupled and coordinated development of China’s green economy efficiency and new-type urbanization under the dual-carbon goal - Zhu, Xi; Wei, Yuangu; Gui, Qingqing; Yang, Guangming; Qin, Yizhi; Cheng, Siyi (Frontiers in Environmental Science, 2025)
Promoting the coupling and coordinated development of green economic efficiency (GEE) and new-type urbanization (NTU) is of great significance for high-quality regional development. Based on the data of 30 provinces (autonomous regions and municipalities directly under the Central Government) in China from 2006 to 2021, the coupling coordination model is used to measure the coupling coordination level between GEE and NTU, and the Dagum Gini coefficient is used to analyze the difference between the two coupling coordination degrees (CCD). Fuzzy set qualitative comparison analysis (fsQCA) was used to explore the influencing factors of the two from the perspective of configuration, so as to clarify the conditional configuration and multiple paths that drive the improvement of the coupling coordination degree of the two. The results show that: (1) GEE and NTU in China are on the rise in most areas of the country. (2) The CCD between GEE and NTU in China is generally on the rise; The spatial distribution showed a decreasing trend in East China, Central China, Northeast China and West China. (3) The Gini coefficient of CCD between the two shows an overall upward trend, and the overall gap of the coupling relationship is gradually increasing. (4) Openness to the outside world is the core condition of high coupling coordination degree, and the industrial structure-opening to the outside world cooperative and opening to the outside world leading path can produce high coupling coordination degree. According to the provinces and regions of different coordination levels, different policy suggestions are put forward to promote the continuous collaborative development of GEE and NTU.